Approach to the separation of mixtures in Fundamental Education under the CTSA approach aiming contextualization in Science teaching - Vasconcelos, Carlos Alberto (2017)
Discussions of topics related to Science and Technology have occupied a prominent position in the current society. In the Brazilian educational scenario, specifically in the field of science teaching, this has had repercussions on proposals and reforms. In view of the above, an experiential analysis was conducted with a discussion about a didactic sequence regarding the content of Mixtures under the CTSA approach, in a Elementary School. From this analysis, it was verified that the students were able to interrelate the content with scientific, technological, social and environmental aspects; That the incorporation of pedagogical practices by educators stimulates learning through the use of scientific knowledge in the exercise of citizenship and promotes the intellectual development of the student with criticality.